Climate change, food security, and central banks in developing economies - Arndt, Channing; Hartley, Faaiqa; Loewald, Christopher; Makrelov, Konstantin (T20 Italy, 2021)
Climate change represents a rapidly emerging challenge for central banks, particularly in developing economies. Central banks have tools to increase the economy’s resilience, enable reallocation of resources to reduce costs and grasp opportunities, and smooth the transition to a low carbon economy. Specific measures, such as changes to selected macroprudential rules, merit consideration. The climate challenge also highlights two traditional mandates. First, price and financial stability support investment and long-term price discovery, both crucial to climate response. Second, central banks are already critical providers of information to public and private decision-makers. Creation and dissemination of knowledge that facilitates improved decision-making by public and private actors (notably investors) may be central banks’ most important contribution to more favourable social, economic, and environmental outcomes in a context of climate change. The T20 can play important roles in facilitating this knowledge acquisition by central banks in developing countries.